Severe Multi-Organ Failure and Hypereosinophilia: When to Call It "Idiopathic"? - Massimo Radin MD; Luca Bertero MD; Dario Roccatello MD; Savino Sciascia MD, PhD (SAGE Publishing, 2018)
The hypereosinophilic syndrome is a rare disease characterized by the association between high absolute eosinophil count and eosinophil-mediated organ damage. We describe a case of a 70-year-old male with an absolute eosinophil count of 2130 cells/µL. Clinical symptoms and signs included the following: severe asthenia, axonal sensitive motor neuropathy, basal pleural effusion with signs of hypoventilation on chest radiography, and gastrointestinal symptoms such as severe diarrhea, weight loss (−10 kg in 6 months), abdominal pain, and vomiting. On physical examination he had an urticarial dermatitis on his back, abdomen, and lower limbs. An extensive instrumental and laboratory diagnostic workup was performed. When all causes of primary and secondary hypereosinophilic syndrome were excluded, treatment with solumedrol infusion and oral prednisone was started, with a rapid recover of clinical symptoms and normalization of laboratory parameters. A complete remission of the laboratory and clinical findings was achieved after 2 months and maintained over 1-year follow-up.